(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
In order to promote innovation activities in the agro- bio technological sector, regulatory policies must guarantee to the industry the access to natural and biological resources located into indigenous ecosystems. On the other hand, it is necessary to conceal the Intellectual Property Rights based on those resources –patents or plantbreeders system- with the protection of indigenous style of life. Also, the present paper studies the difficulties of protect the traditional knowledge of indigenous communities by IPR.